CORPORATE IMAGE BERBASIS CORPORATE SOCIAL RESPONSIBILITY, TRUST DAN SOCIAL ENGAGEMENT DI CV. EL-HANIF PUTRA MANDIRI GROUP MAGELANG - Sahni, Sahni; Sulistyo, Heru (Penerbit Lafadz Jaya, 2025)
This study aims to analyze how to improve corporate image, which is very important for companies to increase competitiveness in the business world. Corporate image is analyzed based on corporate social responsibility (CSR), trust, and social engagement. The study uses a quantitative approach with an explanatory research method. A sample of 138 people was selected through purposive sampling techniques from residents around the company. Data was collected by distributing questionnaires and analyzed using the Partial Least Squares (PLS) method. The results of the study indicate that CSR has a significant positive effect on corporate image, trust, and social engagement. Social engagement is proven to have a significant positive effect on corporate image, while trust does not have a significant effect on corporate image. These results indicate that social engagement is more decisive in determining public perception of corporate image compared to trust. The results of this study also provide implications that companies need to strengthen the sustainability of CSR programs and strengthen social engagement to improve a positive corporate image in the eyes of residents around them.